MICROFILTRATION MEMBRANES MODIFIED WITH HYDRATED ZIRCONIUM DIOXIDE CONTAINING CARBON NANODOTS - КУДЕЛКО, К. О.; РОЖДЕСТВЕНСЬКА, Л. М.; ВЕРБИЦЬКА, А. А.; БОРИСЕНКО, Ю. В.; БАРСУКОВ, В. З. (Technologies and Engineering, 2023)
Purpose: Establishing the influence of modifiers (hydrated zirconium dioxide and its composite with carbon nanodots) on the rejecting ability of polymer membranes (ion transport and features of filtration of water and protein solutions) for the further use of membranes with the best properties in the processes of concentrating protein components from liquids of biogenic origin. Methods: Scanning electron microscopy (study of the membrane morphology), gravimetric (determination of the ZrO2 content in the polymer), conductometry (salt content in aqueous solutions), potentiometry (the measurements of membrane potential), spectrophotometry (protein concentration in the permeate). Results: Microfiltration membranes (polyvinylidenefluoride and polyamide) were modified with hydrated zirconium dioxide, as well as its composite with carbon nanodots, the size of which is 8–12 nm. Testing during water filtration showed that polyvinylidenefluoride membranes (both original and modified ones) demonstrate´the lowest hydrodynamic resistance, which is (0.48-3.77)´1012m-1. When filtering a solution of bovine serum albumin occurred, it was shown that the membrane modified with a composite is characterized by the highest resistance against organic pollutants and the highest rejecting ability: 100% of the protein is retained. This membrane was used to obtain the protein concentrate of milky whey. At the same time, sediment is formed on its outer surface. To identify carbon nanodots in the incorporated composite, an indirect method has been proposed. It involves measuring the membrane potential and studying the diffusion of salt (1,1 electrolyte). The diffusion coefficients of ions were calculated. In the case of polyvinylidenefluoride materials containing one- or two component modifiers, these values are 7´10-12 and 6´10-13 м2с-1 respectively for Na+ ions. Thus, the carbon constituent decreases the diffusion coefficients by an order of magnitude. Conclusions: The insertion of a two-component modifier containing carbon nanodots into the pores of microfiltration membranes allows one to improve the retention capacity of the membranes and increase their resistance against organic pollutants. Membranes can be used for processing liquids of biogenic origin.